MULTILINGUALISM: A LINGUISTIC DETERMINISM PERSPECTIVE ON ONE ARRANGED MURDER - Mhaiskar, Rahul Naibharosa (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This paper explores the intersection of linguistic determinism and multilingualism in Chetan Bhagat’s One Arranged Murder, a novel set in the multicultural landscape of contemporary India. Drawing on the Sapir-Whorf Hypothesis, it examines how the integration of Punjabi and Hindi within an English narrative shapes character development, cultural authenticity, and the representation of Indian multilingual identity. Bhagat’s use of vernacular terms, food references, and kinship expressions reflects the sociolinguistic diversity of India and enriches the narrative with cultural nuance. Code-mixing and grammatical adaptations, such as English plural markers applied to Hindi-origin words, illustrate the dynamic interplay of language and identity in urban, multilingual contexts. The paper analyses dialogues, cultural practices, and kinship terms to demonstrate how linguistic choices influence thought processes and interpersonal dynamics. By highlighting the narrative potential of multilingualism, this study underscores the role of language as a powerful tool for reflecting the complexities of a diverse society.Keywords: Linguistic Determinism, Multilingualism, Sapir-Whorf Hypothesis, Indian English Literature, Cultural Identity